FORMATION PECULIARITIES OF PHONOLOGICAL KNOWLEDGE AT STUDENTS WITH SEVERE SPEECH DISORDERS - Melnichenko, Tatiana V. (Educological discourse, 2016)
The article is devoted to the study of peculiarities formation of phonological knowledge at students with severe speech disorders (SSD) in special educational institutions in the process of mastering school knowledge. Theoretical analysis of linguistic, psychological, educational, speech therapy, psycholinguistic and methodical literature on the study showed that the problem of formation of language and speech competence of students with SSD is relevant, but understudied. Determined that the phonological structure includes sufficient knowledge generated phonemic perception, phonemic representation, auditory attention and control, sound analysis and synthesis. In intelligence indicated that a sufficient number of phonological knowledge on a practical level is manifested in the ability to perceive the actual speech and speech of others, select the required phonemes for their combination of words and their expression, the ability to isolate a sound of words, sentences of text, the ability to control their speech and correct errors, and so on. Indicated that on the basis of knowledge of students with severe speech disorders acquire lexical, grammatical and syntactical knowledge and skills, which are formed in the designated category with a kind of specificity and complexity.